Case of study: The windmill of el pasico: alive cultural heritage - Antonio Martínez-Pando, José (Seven Editora, 2023)
The Campo of Cartagena counts on an excellent rural heritage not only for its monumental and landscaping values but also for its material and immaterial heritage. Of all of these monuments, the windmill of El Pasico highlights for its wonderful state of conservation, for being a symbol of its proud town and for being a cultural, touristic and leisure resource. DOI: 10.56238/pacfdnsv1-009